Transfer kinetics from colloidal drug carriers and liposomes to biomembrane models: DSC studies - Maria Grazia Sarpietro; Francesco Castelli (Wolters Kluwer Medknow Publications, 2011)
The release of bioactive molecules by different delivery systems has been studied. We have proposed a protocol that takes into account a system that is able to carry out the uptake of a bioactive molecule released during the time, resembling an in vivo-like system, and for this reason we have used biomembrane models represented by multi-lamellar and unilamellar vesicles. The bioactive molecule loaded delivery system has been put in contact with the biomembrane model and the release has been evaluated, to consider the effect of the bioactive molecule on the biomembrane model thermotropic behavior, and to compare the results with those obtained when a pure drug interacts with the biomembrane model. The differential scanning calorimetry technique has been employed. Depending on the delivery system used, our research permits to evaluate the effect of different parameters on the bioactive molecule release, such as pH, drug loading degree, delivery system swelling, crosslinking agent, degree of cross-linking, and delivery system side chains.